2019
DOI: 10.2147/cmar.s228843
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Validation of the Chinese Version of the Shame and Stigma Scale in Patients with Head and Neck Cancer</p>

Abstract: PurposeHead and neck cancer (HNC) patients suffer from perceived shame and stigma due to the illness diagnosis, as well as disfigurement following surgery. To measure HNC patients’ perception of shame and stigma, the Shame and Stigma Scale (SSS) was developed and preliminarily validated. In this study, we aimed to translate, adapt, and validate the SSS in Chinese.MethodsThis study consisted of a cross-sectional design with consecutive sampling and consisted of two stages: (1) translation of the SSS into Chines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 39 publications
1
16
2
Order By: Relevance
“…In a study that reported on development of a scale to measure shame and stigma in HNC patients, greater perceived stigma as measured by items such as "people avoid me because of my cancer" and "I sense that others feel strained when around me," was associated with increased psychological difficulties including depression and demoralisation, and inversely related to quality of life (Kissane et al, 2013). These findings were replicated in a Taiwanese HNC sample that found greater stigma associated with depression and anxiety (Tseng et al, 2019).…”
Section: The Psychological Impact Of Stigma On Individuals With Canmentioning
confidence: 90%
See 1 more Smart Citation
“…In a study that reported on development of a scale to measure shame and stigma in HNC patients, greater perceived stigma as measured by items such as "people avoid me because of my cancer" and "I sense that others feel strained when around me," was associated with increased psychological difficulties including depression and demoralisation, and inversely related to quality of life (Kissane et al, 2013). These findings were replicated in a Taiwanese HNC sample that found greater stigma associated with depression and anxiety (Tseng et al, 2019).…”
Section: The Psychological Impact Of Stigma On Individuals With Canmentioning
confidence: 90%
“…Of the 16 studies included in the review, ten were qualitative investigations conducted by telephone or in-person interviews and all were moderate to high quality. The remaining six quantitative studies ranged from low to high quality; two described the development of a stigma scale (Kissane et al, 2013;Tseng et al, 2019), one investigated quality of life (QOL) in cancer patients with disfigurement (Arunachalam et al, 2011), one investigated perceived (felt) stigma in laryngectomy patients (Devins, Stam, & Koopmans, 1994), another investigated the effect of breast asymmetry following cancer treatment (Waljee et al, 2008) and the final study compared the psycho-social impact of stigma in lung to HNC cancer patients (Lebel et al, 2013). Most of the studies examined HNC cancers (n = 11) with the remainder investigating breast or a combination of various cancers.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…So far only three studies have been conducted on shame and stigma for head and neck cancer. The first study was conducted by Kissane et al authors developed the scale (Kissane et al 2013), the second study was conducted by Pirola et al in which authors translated the scale in Brazil language (Pirola et al 2017), and the third study was conducted by Tseng et al in which authors translated the scale into the Chinese language (Tseng et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Traditional Translation Method Traditional translation was carried using modified guidelines defined in previous studies (Beaton et al 2000;Tseng et al 2019). The translation process was conducted into two phases:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation